Mesoscale Eddies Modulate Mixed Layer Depth Globally. Issue 3 (1st February 2019) - Gaube, Peter; J. McGillicuddy, Dennis; Moulin, Aurélie J.
Abstract: Mesoscale eddies, energetic vortices covering nearly a third of the ocean surface at any one time, modulate the spatial and temporal evolution of the mixed layer. We present a global analysis of concurrent satellite observations of mesoscale eddies with hydrographic profiles by autonomous Argo floats, revealing rich geographic and seasonal variability in the influence of eddies on mixed layer depth. Anticyclones deepen the mixed layer depth, whereas cyclones thin it, with the magnitude of these eddy‐induced mixed layer depth anomalies being largest in winter. Eddy‐centric composite averages reveal that the largest anomalies occur at the eddy center and decrease with distance from the center. Furthermore, the extent to which eddies modulate mixed layer depth is linearly related to the sea surface height amplitude of the eddies. Finally, large eddy‐mediated mixed layer depth anomalies are more common in anticyclones when compared to cyclones. We present candidate mechanisms for this observed asymmetry. Plain Language Summary: Mesoscale eddies, rotating bodies of water that can be hundreds of kilometers across and reach thousands of meters into the ocean interior, are found nearly everywhere in the ocean. These eddies are know to transport vast amounts of heat, salt, and ocean life across hundreds to thousands of kilometers. This study investigates how these eddies control the depth to which the surface of the ocean is mixed. Wind and the transfer of heat between the ocean and atmosphere are two of the primary ways in which the ocean surface is homogenized. The depth of this mixed layer, the mixed layer depth, is shown to be deeper in eddies that are warm, when compared to their surrounds, and shallower in cold eddies. We show that the stronger or more energetic the eddies are, the larger their influence is on mixed layer depth. Key Points: Anticyclonic and cyclonic eddies are observed to deepen and shoal the mixed layer, respectively The largest eddy‐induced MLD anomalies are observed during the winter in regions of large eddy amplitude Observations reveal that larger MLD anomalies are more common in anticyclones versus cyclones